2011
DOI: 10.1007/s00244-011-9659-x
|View full text |Cite
|
Sign up to set email alerts
|

Elemental Contaminants in Livers of Mute Swans on Lakes Erie and St. Clair

Abstract: Contaminant inputs to the lower Great Lakes (LGL) have decreased since the 1960s and 1970s, but elemental contaminants continue to enter the LGL watershed at levels that are potentially deleterious to migratory waterfowl. Mute swans (Cygnus olor) using the LGL primarily eat plants, are essentially nonmigratory, forage exclusively in aquatic systems, and have increased substantially in number in the last few decades. Therefore, mute swans are an ideal sentinel species for monitoring elemental contaminants avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
15
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 48 publications
2
15
0
Order By: Relevance
“…The result obtained for the third individual (given as the lower limit in Table 2) differed from the other two values, which resulted from starvation of this individual. Other researchers, who examined mute swans from northern Europe and North America (Clausem and Wolstrup, 1978;Schummer et al, 2011), have also reported concentrations of Cu comparable to those that we found in two of the examined birds. It is worth noting that the 2 specimens of mute swans mentioned here were in very good condition and were killed as a result of hitting electric tractions.…”
Section: Toxic Elementssupporting
confidence: 89%
See 1 more Smart Citation
“…The result obtained for the third individual (given as the lower limit in Table 2) differed from the other two values, which resulted from starvation of this individual. Other researchers, who examined mute swans from northern Europe and North America (Clausem and Wolstrup, 1978;Schummer et al, 2011), have also reported concentrations of Cu comparable to those that we found in two of the examined birds. It is worth noting that the 2 specimens of mute swans mentioned here were in very good condition and were killed as a result of hitting electric tractions.…”
Section: Toxic Elementssupporting
confidence: 89%
“…The result obtained for the single kestrel individual is also noteworthy ( Table 2). It has been reported that wetland birds can accumulate much larger amounts of copper than terrestrial birds (Horai et al, 2007;Schummer et al, 2011). Horai et al (2007) found concentrations of copper as high as 4970 and 2420 mg/kg d.m.…”
Section: Toxic Elementsmentioning
confidence: 99%
“…Earlier reports concerning the Western reef heron indicate a mean Cr concentration of 1.05 µg/g dw . A slightly higher concentration of Cr was found in the livers of mute swan Cygnus color from the Lower Great Lakes (geometric means range: 1.30-1.65 mg/kg dw) (Schummer et al, 2011).…”
Section: Discussionmentioning
confidence: 86%
“…During the pre-laying period, black-headed gulls forage almost exclusively on the remains of aquatic plants as well as aquatic and terrestrial invertebrates, but only occasionally on fish (Vernon 1972; Cramp and Simmons 1983; P. Indykiewicz, unpublished data). A diet rich in aquatic plants and animals promotes a high accumulation of Cu in the liver (Eisler 1998; Xue et al 2010; Schummer et al 2011; Horai et al 2007), from which it might be relocated to the eggs. This type of food becomes increasingly available to black-headed gulls as the vegetation period progresses.…”
Section: Discussionmentioning
confidence: 99%